Understanding the Dalit of Sariaya, Quezon, Philippines - Trinidad, Sol Maris T.
This paper aims to explore the definition of dalit and its practice specifically in Barangay Concepcion Palasan, Sariaya, Quezon. This will also touch on the dalit connection with the planting cycle of the community. Dalit is a hymn of praise to San Isidro Labrador, and is sung as pre-planting prayers. The nine days of praying the novena is repeated three times. The novena starts at the house of the designated host and is also sung during processions where the image of the saint is brought to the next house. The procession is repeated everyday for twenty-seven days.